Genetic diversity of SARS-CoV-2 infections in Ghana from 2020-2021 - Collins M. Morang’a; Joyce M. Ngoi; Jones Gyamfi; Dominic S. Y. Amuzu; Benjamin D. Nuertey; Philip M. Soglo; Vincent Appiah; Ivy A. Asante; Paul Owusu-Oduro; Samuel Armoo; Dennis Adu-Gyasi; Nicholas Amoako; et al. (Nature Communications, 2022)
In this genomic epidemiology study from Ghana, the authors sequence ~1,000 SARS-CoV-2 whole genomes from March 2020 to September 2021. They describe changes in the predominant circulating lineages over time and infer how variants of concern were likely introduced into the country.